Until angels close my eyes - McDaniel, Lurlene (New York : Bantam Books, 1998)
Leah learns her stepfather has cancer and she contemplates losing the first real family she's ever known, so she finds comfort in a visit to Amish country to see her beloved Ethan.
600
Accelerated Reader AR
Keywords: Cancer -- Juvenile fiction; Amish -- Juvenile fiction; Christian life -- Juvenile fiction